International access to research infrastructure in the Arctic. (1st September 2022) - Ruck, Kate; Arndal, Marie Frost; Biebow, Nicole; Dahl, Justiina; Flått, Stig; Granskog, Mats; Holste, Svenja; Lenz, Josefine; Mercer, Jennifer; Pausch, Franziska; Perttu, Anna-Maria; Rasch, Morten; et al.
Abstract: Reliable access to Arctic research infrastructure is critical to the future of polar science. In cultivating proposals, it is essential that researchers have a deep understanding of existing platforms when selecting the appropriate research site and experimental design for projects. However, Arctic infrastructure platforms are often funded as national assets, and choices for what would be the best platform for the project are sometimes at odds with a researcher's ability to gain access. Researchers from Arctic and non-Arctic nations are poised to benefit from reducing barriers and increasing cooperation around transnational access to Arctic infrastructure, allowing scientists to successfully execute the research that is most needed rather than what is just logistically feasible. This commentary provides a summary of findings from a workshop held at the 2021 Arctic Science Summit Week to discuss navigating "transnational" or "cross-border" access to national research infrastructure. This workshop brought together users and operators of Arctic infrastructure platforms with the three goals of identifying challenges, best practices, and possible next steps for improved collaboration.